Machine Learning Approaches to Forecasting the Winner of the 2024 NBA Championship - Zadravec, Hana (Proceedings of the10th Student Computing Research Symposium (SCORES’24), 2024)
Forecasting the winner of the NBA Championship has become more important as there is a large amount of data and the league’s popularity is increasing. This research investigates techniques in machine learning to predict the winner of the 2024 NBA Champi-onship. Three methods - random forest regression, SVR, and linear regression - are used and assessed. The process includes scrap-ing data from Basketball Reference, then analyzing and selecting features. Findings show the leading projected teams for 2024 ac-cording to each model, with random forest regression showing the best prediction. Analysis of feature importance emphasizes critical predictors like team quality rating and player performance metrics. The research highlights the capabilities of machine learning in pre-dicting sports outcomes and indicates areas for additional research to improve predictions.